2002
DOI: 10.21273/hortsci.37.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Cyanamide Accelerates Vegetative Budbreak and Shortens Fruit Development Period of Blueberry

Abstract: Experiments were conducted in north Florida and south Georgia to determine the effects of H2CN2 sprays on vegetative and reproductive growth of blueberry. In Florida, mature, field-grown `Misty' southern highbush (Vaccinium corymbosum L. hybrid) blueberry plants were sprayed to drip with 0, 10.2, or 20.4 g·L-1 of H2CN2 [hereafter referred to as 0%, 1.0%, and 2.0% (v/v) H Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 8 publications
2
14
0
1
Order By: Relevance
“…The numbers of lateral vegetative budbreaks per centimeter of shoot length were increased by hydrogen cyanamide sprays for both cultivars and in both years (Tables 1-3). This result was expected and is consistent with known responses of southern highbush blueberry to hydrogen cyanamide (Williamson et al, 2001(Williamson et al, , 2002. In Expt.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The numbers of lateral vegetative budbreaks per centimeter of shoot length were increased by hydrogen cyanamide sprays for both cultivars and in both years (Tables 1-3). This result was expected and is consistent with known responses of southern highbush blueberry to hydrogen cyanamide (Williamson et al, 2001(Williamson et al, , 2002. In Expt.…”
Section: Resultssupporting
confidence: 91%
“…Hydrogen cyanamide has been used in blueberry production in the southeast United States to stimulate leaf growth and advance the ripening date of blueberries Williamson et al, 2001Williamson et al, , 2002. During these earlier experiments, observations revealed that poorly timed hydrogen cyanamide applications resulted in significant flower bud mortality, even though leaf growth was readily stimulated.…”
mentioning
confidence: 99%
“…The points where the dashed lines cross the percent Bloom curves is where Spier 1985), it is likely that the chilling requirement of both cultivars had been met before the date at which GDD calculation began. Additionally, the use of hydrogen cyanamide helps satisfy the chilling requirement, although other effects of this chemical include increased rate of flower bud opening in the spring (Williamson et al, 2002). However, this latter effect would affect both cultivars similarly.…”
Section: Discussionmentioning
confidence: 99%
“…A delay in the onset of vegetative growth resulting from a lack of chilling would only exacerbate this problem. This situation may occur during mild winters in the southeast United States (Mainland, 1984;Williamson et al, 2002) and could be worsened by closing a high tunnel too early, potentially preventing the accumulation of chill hours. The situation is further complicated by the fact that some negation of chilling may occur if high temperatures occur during critical months (Lyrene and Williamson, 2004) as is likely in high tunnels.…”
Section: Discussionmentioning
confidence: 99%